Disproportionately increased 24-h energy expenditure and fat oxidation in young men with low birth weight during a high-fat overfeeding challenge. - Brøns, Charlotte; Lilleøre, Søren; Astrup, Arne; Vaag, Allan (European Journal of Nutrition, 2016)
Background: Low birth weight (LBW) associates with increased risk of developing type 2 diabetes. LBW individuals exhibit disproportionately reduced peripheral insulin action and increased fat oxidation after a 5-day high-fat overfeeding (HFO) challenge. Furthermore, LBW men exhibit increased nocturnal fat oxidation during energy balance and low energy expenditure (EE) during fasting. We hypothesized that short-term HFO could further unmask key defects of whole-body energy metabolism in LBW men. Methods: Eighteen LBW (2717 ± 268 g) and 26 normal birth weight (NBW) (3893 ± 207 g) healthy young men were included in a 5-day HFO (60 E % fat, +50 % calories) study. The 24-h EE, respiratory quotient and substrate oxidation rates were assessed by indirect calorimetry using respiratory chambers. Results: After adjusting for body composition, the LBW subjects displayed increased nighttime EE ( P = 0.02) compared with NBW controls during HFO. Nighttime glucose oxidation rate was decreased ( P = 0.06, adjusted P = 0.05), while both adjusted 24-h ( P = 0.07) and nighttime ( P = 0.02) fat oxidation rate was elevated in LBW subjects. The relative contribution of fat oxidation to EE was increased in LBW compared with NBW men during the entire 24-h period ( P = 0.06) and during nighttime ( P = 0.03). Conclusions: We suggest that disproportionally enhanced fat oxidation in LBW individuals during short-term HFO represents a compensatory response to reduced subcutaneous adipose tissue expandability and storage capacity. The extent to which this mechanism may lead to, or be replaced by insulin resistance, ectopic fat accumulation and/or glucose intolerance during long-term HFO in LBW needs further studies.